Formulasi nugget ikan curah berdasarkan karakteristik organoleptik dan fisik - Choirul Anam; Ana Amiroh; Mariyatul Qibtiyah; Astrid Gita Karina; Ardiyan Dwi Masahid; Yuli Witono (Agroindustrial Technology, University of Trunojoyo Madura, 2023)
The utilization of trash fish is not optimal for animal feed, and the price falls during the main harvest. To increase the selling value, the fish processing technology is needed. This research aimed to determine the organoleptic and physical characteristics of bycatch fish nuggets with variations in fish species and flour concentration so the best formulations were obtained and chemical characteristics were known. This experiment research with two factors, the type of fish (A) and the ratio between fish and flour (B). Factor A, namely A1 (Peperek fish); A2 (Juwi fish); A3 (Tembang fish). Factor B, namely B1 (40: 60); B2 (50: 50); B3 (60: 40). Data processing uses SPSS version 20. If the results of the analysis of variance show significant differences, the Tukey test will be continued. Based on organoleptic results, bycatch fish nuggets still had a fairly good product reception by the panelist. The bigger addition of flour affected the brighter color and harder texture. Based on the effectiveness test of this research, the best formulation nugget was the A2B1 formulation (Juwi fish nuggets with 40:60 fish and flour formulations as fillers) with an effective value of 5,78. The best formulation bycatch fish nugget had a water content of 58.99%; ash content of 1.50%; fat content of 1.11%; protein content of 8.55%; and carbohydrate content of 29.85%. These values were following the standards set by SNI 7758-2013 about fish nuggets